2014
DOI: 10.1039/c4ra06383j
|View full text |Cite
|
Sign up to set email alerts
|

One step preparation of porous polyurea by reaction of toluene diisocyanate with water and its characterization

Abstract: Porous polyurea is synthesized by reacting toluene diisocyanate with water in a water–acetone binary solvent. Materials characterization led to the likely conformations of the polymer chains owing to presence of intensive H-bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 67 publications
1
53
0
Order By: Relevance
“…The XRD data of the aromatic polyurea revealed that the material was mainly amorphous. Very broad but characteristic reflexes were observed at 2θ = ≈11 and ≈22°. For the aliphatic polyurea nanocapsules, the reflexes were sharper than those for the aromatic system and the degree of crystallinity was evaluated to be about 55%.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The XRD data of the aromatic polyurea revealed that the material was mainly amorphous. Very broad but characteristic reflexes were observed at 2θ = ≈11 and ≈22°. For the aliphatic polyurea nanocapsules, the reflexes were sharper than those for the aromatic system and the degree of crystallinity was evaluated to be about 55%.…”
Section: Resultsmentioning
confidence: 98%
“…The aliphatic polyurea is known to exhibit a higher degree of crystallinity compared to an aromatic polyurea based on the monomers TDI and DAB. As in TDI the diisocyanate groups are angled, the degree of crystallinity is reported to be rather low . However, a higher degree of crystallinity is expected to increase the encapsulation efficiency .…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectrum of PUCorr‐1 (Figure a) shows the presence of C═O stretching of the urea linkage at 1,650 cm −1 , and a substituted –NH stretching at 3,350 cm −1 . The strong absorption band at 1,550 cm −1 represents –NH bending, whereas the –CH stretching band appeared around 3,000 cm −1 …”
Section: Resultsmentioning
confidence: 99%
“…However, this crosslinking reaction is believed not to occur because specific conditions (high temperature, catalyst) are required for this reaction [18,19]. Obviously, there are two types of linear PU formed in this polymerization as described above, and the chain of the PU from the reaction of TDI with water is likely more rigid than that from the reaction of TDI with EDA based on its chemical structure as shown in Fig.…”
Section: Mechanism Of Pu Formation By Tdi Reactionsmentioning
confidence: 99%